Urinary Soluble CD163 Levels Predict IgA Nephropathy Remission Status - Gong, Shaomin; Jin, Shi; Li, Yang; Jiang, Wuhua; Zhang, Zhen; Shen, Ziyan; Wang, Jialin; Zhou, Huili; Liu, Xiao; Xu, Xialian; Ding, Xiaoqiang; Shi, Yiqin; et al. (Frontiers in Immunology, 2021)
Noninvasive biomarkers of disease activity are needed to predict disease remission status in patients with IgA nephropathy (IgAN). Soluble CD163 (sCD163), shed by monocytes and macrophages, is a potential biomarker in diseases associated with excessive macrophage activation. We investigated the association of urinary sCD163 (u-sCD163) with histopathological activity and clinical manifestations in 349 patients with biopsy-diagnosed IgAN. U-sCD163 was measured via enzyme-linked immunosorbent assay. In patients with IgAN, higher u-sCD163 levels were associated with histological lesions of greater severity, as well as more proteinuria and poorer renal function. Additionally, u-sCD163 was correlated with infiltration of tubulointerstitial CD163+ macrophages. High u-sCD163 levels (＞3.57 ng/mg Cr) were associated with a 2.66-fold greater risk for IgAN remission failure in adjusted analyses. Adding u-sCD163 levels to the model containing clinical data at biopsy and MEST-C score significantly improved the risk prediction of IgAN remission status (AUC 0.788). Together, our results suggest that u-sCD163 may be a useful noninvasive biomarker to evaluate disease severity and remission status of IgAN.